Analysis of References in the Collection of Short Stories of Menghardik Drizzle by Sapardi Djoko Damono - Jumiati Jumiati; Erni; Rian Hidayat (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Discourse is the most complete language unit because in discourse there are relationships between sentences that meet grammatical requirements, namely cohesion (form) and coherence (meaning). Cohesion is divided into two aspects, namely grammatical cohesion and lexical cohesion. There are four grammatical cohesion markers, namely references, substitutions, ellipsis, and conjunctions. Sumarlam (2009) classifies references into three, namely personal references, demonstrative references, and comparative references. The problem in this research is how to use persona reference, demonstrative reference and comparative reference in the collection of short stories Menghardik Gerimis by Sapardi Djoko Damono?. The purpose of this study is to describe, analyze, and interpret the use of persona reference, demonstrative reference and comparative reference in the collection of short stories Menghardik Gerimis by Sapardi Djoko Damono. This study uses a qualitative research approach and content analysis methods. The theory used in this research is : Sumarlam (2009), Abdul Chaer (2011), Kushartanti, dkk (2009), Fatimah Djajasudarma (2006), Masnur Muslich (2010), Eko Sugiarto (2014) dan Yayat Sudaryat (2009). The data of this research are persona reference, demonstrative reference and comparative reference contained in the 17 short stories by Sapardi Djoko Damono. The result of the research on the use of persona reference found as many 449 data in 17 short stories, 54 data demonstrative reference in 15 short stories, and 12 data comparative references in 7 short stories. The use of all the reference gramatical cohesion elemants has functioned as a reference (persona, demonstrative, comparative) in accordance with the language element (endophores/exophores).